2016
DOI: 10.1111/evj.12563
|View full text |Cite
|
Sign up to set email alerts
|

Proximal suspensory desmopathy in hindlimbs: A correlative clinical, ultrasonographic, grosspost mortemand histological study

Abstract: Ultrasonography was reliable for the detection of SL pathology based on histology as the gold standard. Adhesions may be a reason for recurrent lameness after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…The greatest variation was seen in the shape, distribution, and signal intensity of the central and peripheral muscle and adipose tissue. Decrease in signal intensity of the muscle and adipose tissue has been related to injury and a recent study has highlighted the frequency of occurrence of muscle pathology in association with proximal suspensory desmopathy . It has previously been demonstrated that intermediate signal intensity within the suspensory ligament is related to the presence of muscle tissue, the distribution, and amount of which showed considerable variation .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The greatest variation was seen in the shape, distribution, and signal intensity of the central and peripheral muscle and adipose tissue. Decrease in signal intensity of the muscle and adipose tissue has been related to injury and a recent study has highlighted the frequency of occurrence of muscle pathology in association with proximal suspensory desmopathy . It has previously been demonstrated that intermediate signal intensity within the suspensory ligament is related to the presence of muscle tissue, the distribution, and amount of which showed considerable variation .…”
Section: Discussionmentioning
confidence: 99%
“…The size of the suspensory ligament, its proximity to the metatarsal bones and comparison with the contralateral limb (if lameness is unilateral) may aid interpretation. Adhesions between the suspensory ligament and either the adjacent soft tissue structures or the metatarsal bones may occur in association with proximal suspensory desmopathy and knowledge of normal MR anatomy may facilitate their identification …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All limbs selected for the study had no history of preexisting pathology of the hind limb PSL. In horses with PSLD, adhesions may form between PSL and proximoplantar aspect of the metatarsal bone or the surrounding tissue . In addition, chronic inflammation of the metatarsal fascia results in thickening of this structure, which can impede the cutting capacity of the instrument used to incise it.…”
Section: Discussionmentioning
confidence: 99%